Embedding integration: how European integration splits mainstream parties - Whitefield, S; Rohrschneider, R (SAGE Publications, 2019)
While newly contested issues connected with internationalism, such as European integration and migration, have become more politically salient, much of the literature sees these as largely the domain of ideologically extremist and challenger parties. By contrast, building on work by Kriesi et al, this paper argues that international issues are far more embedded in party stances across the leftright spectrum than the niche and extremist models or Kriesi et al suggest. Accordingly, we develop a typology for categorising parties according to their stances on left-right ideology and their positions on integration. Our analysis employs expert surveys on the stances of all electorally significant parties conducted in 24 European countries in 2013. The results have important implications for understanding the impact of international issues on how parties now appeal to voters.